Caspase 3 inactivation protects against hepatic cell death and ameliorates fibrogenesis in a diet induced NASH model - Thapaliya, Samjhana (Dig Dis Sci, 2014)
BACKGROUND/AIMS: Hepatocyte cell death is a key feature of nonalcoholic steohepatitis (NASH). As the contribution of specific caspases remains unclear, our aim was to ascertain the effect of caspase 3 suppression on liver injury and fibrogenesis. METHODS: C57BL/6 wild-type (WT), and caspase 3 knock out (Casp3(−/−)) mice were placed on a methionine- and choline-deficient (MCD) diet for 6 weeks to induce steatohepatitis and liver fibrosis. Thereafter, liver injury, liver fibrosis and hepatocellular apoptosis were quantified in liver sections. Additionally, expression of proteins associated with liver inflammation and fibrogenesis were analyzed. RESULTS: WT mice fed MCD diet showed marked activation of caspase 3 in hepatocytes, in conjunction with steatohepatitis and increased hepatic triglyceride levels, hepatocyte ballooning, inflammation and fibrosis. Casp3(−/−) fed the MCD diet showed similar serum ALT levels and NAFLD activity scores (NAS) compared to WT MCD-fed mice. However Casp3(−/−) mice on the MCD diet showed a marked reduction in expression of transcripts for pro-fibrogenic genes i which translated into reduced hepatic collagen deposition. These changes were associated with decreased levels of apoptosis, and a significant reduction in the expression of cytokines involved in inflammatory signaling. Casp3(−/−) mice on the MCD showed a reduction in expression of chemokine receptor 2 (CCR2) leading to ameliorated infiltration of inflammatory lymphocyte antigen 6 complex, locus C1 (Ly6c) positive monocytes. CONCLUSION: These findings support a prominent role for hepatocyte caspase 3 activation in NASH related apoptosis, fibrogenesis and fibrosis which in part is mediated via CCR2 dependent infiltration of Ly6c positive monocytes.